Metaverse Marketing: Exploring New Frontiers for Brand Engagement and Consumer Experience - Fachri Afif; Perengki Susanto (Penerbit Jurnal Indonesia, 2025)
The emergence of the metaverse presents novel opportunities and challenges for marketing practices, shifting the landscape of brand-consumer interactions. This research aims to explore the potential of the metaverse as a new frontier for enhancing brand engagement and elevating consumer experiences. Employing a qualitative research approach, this study analyzes existing literature, case studies of early adopter brands, and expert opinions to identify key strategies, benefits, and challenges associated with metaverse marketing initiatives. The findings reveal that the immersive and interactive nature of the metaverse allows for the creation of unique and memorable brand experiences, fostering stronger emotional connections and driving deeper consumer engagement. Virtual events, branded virtual environments, and the integration of virtual goods and services emerge as promising avenues for marketers. However, challenges related to user adoption, ethical considerations, and the need for innovative content creation are also highlighted. In conclusion, the metaverse offers significant potential for marketers to forge new connections with consumers and build brand loyalty, necessitating a strategic and thoughtful approach to navigate this evolving digital landscape.